Pengembangan Destinasi Wisata Alam Pada Perkebunan Karet PT. Lonsum di Desa Tamatto Kabupaten Bulukumba - Sasnita; Firdaus W. Suhaeb (Research Agency for Humanity and Urban, 2023)
This study aims to determine, (1) The role of the Tamatto Village community in developing the natural tourism destination potential of PT. Lonsum, (2) The relationship between visitors and the people of Tamatto Village in the development of natural tourism destinations for PT. Lonsum. This research is a type of development anthropology research with a tourism sector study unit. Data collection techniques, namely primary data obtained through observation and interviews from sources or informants, as well as secondary data obtained through literature studies, books, photo documents and statistics. This study involved 20 informants consisting of visitors to the rubber plantation area, people who live around the rubber plantations, and parties from PT. Lonsum. The results of the study show that: (1) The community has a role in the potential for developing tourist destinations including the role in institutions and the role in monitoring cultural values ​​(2) The relationship between the community and visitors provides positive interrelationships for both of them so that there is a process that creates attraction visitors to local culture in the rubber plantation area.